2014
DOI: 10.3846/btp.2014.404
|View full text |Cite
|
Sign up to set email alerts
|

Employee Reviews on Company Independent Sites and its Impact on Organizational Attractiveness: Role of Information Realism, Person – Environment Fit and Source Credibility Framework

Abstract: Extant literature on recruitment has focused on the traditional sources of recruitment like company brochures, career fairs, and impact of such sources on intent to join the organization, productivity and turnover intention. The influence of recruitment related information on pre hire outcomes is still scarce and inconclusive. With the advent of technology and access to Internet, company websites have become an important source of recruitment. Apart from company websites, job seekers are now using company inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Second, we extend research on how OnERev affect employer attractiveness (Kaur & Dubey, 2014). Our quantitative results support GA2 that OnERev as sources of balanced incongruent signals are detrimental to perceived employer attractiveness.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Second, we extend research on how OnERev affect employer attractiveness (Kaur & Dubey, 2014). Our quantitative results support GA2 that OnERev as sources of balanced incongruent signals are detrimental to perceived employer attractiveness.…”
Section: Discussionmentioning
confidence: 85%
“…So far, few studies have focused on OnERev platforms and their content. Compared to corporate RecW, OnERev are regarded as more credible because they are not controlled by employers (Kaur & Dubey, 2014). A recent analysis of OnERev found that the highest ranked employers received good scores for work atmosphere, teamwork and work content; but poor scores on compensation and leadership (Dabirian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, using this mode could present a potential confound in the study, because it is not digital and inconsistent with the method used to display recruiter political skill to participants. Kaur and Dubey (2014) discussed how, with the increase in the use of technology today, job seekers turn to independent company sites to find out information regarding organizations of interest. Individuals external set up company independent sites to the company in the forms of videos, online reports or blogs.…”
Section: Recruiter Political Skillmentioning
confidence: 99%
“…The person-environment fit (P-E fit) theory of stress is one of the most popular stress theory utilized by organizational researchers in stress studies (Chuang, Shen, & Judge, 2015;Kaur & Dubey, 2014;Nguyen & Borteyrou, 2016). Therefore, is present study uses the P-E fit theory as the underpinning theory for technostress.…”
Section: Applying the Person-environment Fit Theory Of Stress To Techmentioning
confidence: 99%